If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 55 = 2x + 27 Reorder the terms: 55 + 6x = 2x + 27 Reorder the terms: 55 + 6x = 27 + 2x Solving 55 + 6x = 27 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 55 + 6x + -2x = 27 + 2x + -2x Combine like terms: 6x + -2x = 4x 55 + 4x = 27 + 2x + -2x Combine like terms: 2x + -2x = 0 55 + 4x = 27 + 0 55 + 4x = 27 Add '-55' to each side of the equation. 55 + -55 + 4x = 27 + -55 Combine like terms: 55 + -55 = 0 0 + 4x = 27 + -55 4x = 27 + -55 Combine like terms: 27 + -55 = -28 4x = -28 Divide each side by '4'. x = -7 Simplifying x = -7
| 3(4x+5)=17x+12-5x+3 | | 6x+35+9x=15(x+2)-25 | | y+34=19 | | 3-9x=84 | | 5y+12-5=22 | | 2(-x+8)=24 | | 2x^2+162=0 | | 6(x+2)=2(3x+8)-4 | | 3x+4-5x-14=10 | | 7d-4d-4d-6=2d | | 11x+2=14x-10 | | 10y=40x+3xy | | 2(t-2)=6 | | 7x-y=(x) | | 0.5(x+2)-(3x+8)=1.6(x-2)+9 | | 3(7x+20Y)+7(-3x+6y)= | | y-37=-67 | | -21=n-10 | | 2(2x+5)=40 | | 3(x-5)=2(x+1)+x | | 5+9x=-13 | | -5.7-44.2=-8.3v | | -7y+3=8y+1 | | 3(7x+20Y)7(-3x+6y)= | | 4x+8-3x-10=-33 | | -6-2x-1=4x+8-6x-3 | | 2(n+5)=11 | | 7=-11+3(6+5) | | 2(n+5)=111 | | -5r-r=5r-8 | | 3x+5x+4x-2=10 | | -10x+8-6x=-2-17x+9 |